The role of personal social networks on health inequalities across European regions - Craveiro, D. (Health and Place, 2017)
The role of personal social networks on health inequalities is little understood. Theoretically, the characteristics of social network features can contribute to, both, increase and attenuate health inequalities. Few empirical studies that focus on the interaction between socioeconomic position and social networks provide little insight on the topic. Using data from the Survey of Health, Ageing and Retirement in Europe, this study analyses the moderation role of personal social networks on health inequalities in later life among northern, central, and southern European regions. Social advantages of higher socioeconomic individuals are re-enforced by the quality of social connections and the provision of social support. In turn, health inequality is attenuated by marital partnership and participation on social activities that benefits more the health of people at lower socioeconomic positions. Furthermore, results suggest that the influence of social network features on health inequalities is shaped by regions' different policy commitments to familiarization/defamilialization pressures.